Theorizing Institutional Entrepreneuring: Arborescent and rhizomatic assembling. Issue 2 (February 2022) - Gehman, Joel; Sharma, Garima; Beveridge, 'Alim
A growing body of research has cataloged the myriad actors involved in tackling persistent institutional problems. Yet we lack a theoretical toolkit for explicitly conceptualizing and comparing diverse modes of institutional entrepreneuring —the processes whereby actors are created and equipped for institutional action—capable of ameliorating grand challenges. Drawing on assemblage theory, we articulate two ideal-typical modes of assembling actorhood: arborescent and rhizomatic. We differentiate each mode along four principles: association, combination, division, and population. Building on our theorization, we propound an arborescent-rhizomatic space comprising clusters of arborescent, rhizomatic, and hybrid actorhood. To explore the generativity of our framework, we revisit selected research at the intersection of institutional entrepreneurship and grand challenges. We close by articulating how our concept of assembling actorhood reorients research toward institutional entrepreneur ing and contributes to the application of assemblage theory within organization studies.